A Cluster Randomized Trial of Promoting Alternative Thinking Strategies (PATHS®) With Swedish Preschool Children - Eninger, Lilianne; Ferrer-Wreder, Laura; Eichas, Kyle; Olsson, Tina M.; Hau, Hanna Ginner; Allodi, Mara Westling; Smedler, Ann-Charlotte; Sedem, Mina; Gull, Ingela Clausén; Herkner, Birgitta (Frontiers in Psychology, 2021)
The preschool edition of Promoting Alternative THinking Strategies (PATHS®) is a school-based, teacher implemented universal intervention designed to promote social emotional competence (SEC) as a foundation for improved mental health. SEC is a key domain of positive youth development (PYD). PATHS® is delivered as a curriculum and it is based on theories and research regarding SEC, brain development, and optimal school environments. This study was a two-wave pre to posttest, cluster randomized trial with multi-method and informant assessment (N = 285 four and five-year-old Swedish children; 145 wait-list control and 140 intervention, 26 preschools participated in the trial, clusters = 12 intervention schools; clusters = 13 control schools). Within three municipalities, the inclusion criterion was that a participating school must have at least one classroom of 4 to 5-year-old children. Preschools excluded from study participation were open preschools, parent cooperative preschools, and family day homes. After random assignment, schools were informed of condition assignment. Research team members were not blind to schools’ condition assignment. It was hypothesized that relative to children in control schools, children in intervention schools would evidence pre to posttest improvements in social emotional competence (hypothesis 1a, primary outcomes – emotional knowledge/awareness, social problem solving, executive functioning namely, inhibitory control, working memory) as well as other outcomes. Hypothesis, outcomes, and results concern the cluster level (i.e., preschool). Across conditions, the number of participating classrooms per school ranged from one to five, and the number of participating children per classroom was one to 17. Children in PATHS, relative to children in the control, evidenced improvements in working memory and prosocial play, but also showed an increase in hyperactive behaviors. Girls in PATHS, relative to girls in the control, showed improvement in emotional knowledge and reduced anxiety. These results are considered in light of efforts to promote positive development and mental health. The trial registration number at ClinicalTrials.gov is NCT04512157. Main funding was from Swedish Council for Working Life and Social Research, the Swedish Research Council, Formas, and VINNOVA (dnr: 259-2012-71).